Development of high-performance timber-concrete composite floors with reinforced notched connections. (May 2022) - Zhang, Lei; Zhou, Jianhui; Chui, Ying Hei
Abstract: Timber-concrete composite floors with notched connections utilize the complimentary material properties of timber and concrete and exhibit a high level of composite action between two layers. However, due to the low tensile strength of concrete and stress concentration at the notched corners, cracks often develop in concrete at the service load level and can cause the brittle shear failure of concrete notches before the bending strength of timber or concrete is reached. This study presented a novel and efficient reinforcing solution in the notched connections to strengthen the concrete and restrict the crack opening in concrete. Three mass timber panel-concrete composite floors with different levels of reinforcement in the notched connections were fabricated and tested under four-point bending to examine the efficiency of the reinforced notched connections. Test results, including effective bending stiffness, peak loads, and failure patterns were compared with the composite floors without reinforcements in the notches. It was found that the reinforced notched connections improved the ultimate bending stiffness and load-carrying capacity of the composite floors, while the serviceability bending stiffness of the floors was at the same level as the unreinforced floors. The timber members in three reinforced floor specimens failed due to bending while the notched connections only experienced minor damages. With a controlled failure pattern, the use of the reinforced notched connections allows a more accurate prediction of the ultimate load-carrying capacity of the composite floors based on linear elastic analysis.